Method of law istinbath jama'ah al-Nadzir: determination of the beginning of the month of Ramadhan - Sudirman Sudirman; Edi Gunawan; Kasjim Salenda (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
The focus of this research is to reveal the method of istinbath jamaah al nadzir law in determining the beginning of the month. The method research is used descriptive with a qualitative approach. Data was collected by interview to the leadership of jamaah al-nadzir and jamaah al-nadzir society. Prophet bequeathed early determination method can be determined by methods rukyah (saw) and hizab (counting) months. The results showed that jamaah al-nadzir determine the beginning of the month with rukyah method (see) and hizab (counting) in contrast to a predetermined previous scholars. Leaders of jamaah al-nadzir is an absolute determinant beginning and end of the month to see some of them looking directly lunar and see the sea level at high tide and low tide.